Feasibility of Stabilized Zn and Pb Contaminated Soils as Roadway Subgrade Materials - Mingli Wei; Hao Ni; Shiji Zhou; Yuan Li (Advances in Materials Science and Engineering)
The authors have developed a new binder, KMP, which is made from oxalic acid-activated phosphate rock, monopotassium phosphate (KH2PO4), and reactive magnesia (MgO). This study explores the acid neutralization capacity, strength characteristics, water-soaking durability, resilient modulus, and pore size distribution of KMP stabilized soils with individual Zn, Pb, or coexisting Zn and Pb contaminants. For comparison purpose, Portland cement (PC) is also tested. The results show that KMP stabilized soils have a higher acid buffering capacity than PC stabilized soils, regardless of the soil contamination conditions. The water stability coefficient and resilient modulus of the KMP stabilized soils are found to be higher than PC stabilized soils. The reasons for the differences in these properties between KMP and PC stabilized soils are interpreted based on the stability and dissolubility of the main hydration products of the KMP and PC stabilized soils, the soil pore distribution, and concentration of Mg or Ca leached from the KMP and PC stabilized soils obtained from the acid neutralization capacity tests. Overall, this study demonstrates that the KMP is effective in stabilizing soils that are contaminated with Zn or Pb alone and mixed Zn and Pb contaminants, and the KMP stabilized soils are better suited as roadway subgrade material.